2017
DOI: 10.1186/s12907-017-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human epidermal growth factor receptor 2 in bladder urothelial carcinoma

Abstract: BackgroundUrothelial bladder carcinoma (UBC) is one of the most prevalent cancers in men worldwide. Human epidermal growth factor receptor 2 (HER2) expression has been detected in a wide range of urothelial carcinoma. Despite many reports in the literature, the prognostic significance of this overexpression remains unclear. The aim of this study was to assess the expression of HER2 in urothelial bladder carcinomas and its association with clinical and pathological parameters.Methods103 cases of UBC were diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…Most authors agree that IHC could be used as an initial screening tool to triage cases for ISH in BC as well [21,39,[51][52][53], due to the high predictive value and specificity demonstrated by negative immunohistochemical staining for negative gene amplification [19].…”
Section: Issues In Her2 Assessment Methodsmentioning
confidence: 99%
“…Most authors agree that IHC could be used as an initial screening tool to triage cases for ISH in BC as well [21,39,[51][52][53], due to the high predictive value and specificity demonstrated by negative immunohistochemical staining for negative gene amplification [19].…”
Section: Issues In Her2 Assessment Methodsmentioning
confidence: 99%
“…Mammakarzinom deutlich geringer zu sein scheint [33,35]. Daneben sind in einer etwa genauso hohen Frequenz aktivierende Punktmutationen in HER2 (ERBB2) beschrieben.…”
Section: Assoziation Mit Klinisch-pathologischen Parametern (Univariaunclassified
“…We found that HER2 positive rate was high in both CIS (OR = 0.62; 95% CI:0.42-0.92; p = 0.02) [16,17,22,23,25,26,29] (Fig. 2b) and multifocal tumors (OR = 0.45; 95% CI:0.30-0.68; p < 0.01) [16,22,25,26,29] ( (Fig.…”
Section: Oncology-related Featuresmentioning
confidence: 77%
“…2c). HER2 expression was also associated with large tumor size(> 3 cm) (OR = 0.40; 95% CI:0.26-0.63; p < 0.01)[16,20,23,26,29]…”
mentioning
confidence: 99%